2010
DOI: 10.1055/s-0030-1247584
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Idiopathic Hemifacial Spasm with Radiosurgery or Hypofractionated Stereotactic Radiotherapy: Preliminary Results

Abstract: The mean follow-up time of 24 months reported here could be judged too short, and our series too small, but the good results observed so far lead us to underline that, as in trigeminal neuralgia, radiosurgery or hypofractionated stereotactic radiotherapy could represent a therapeutic alternative to microvascular decompression for idiopathic hemifacial spasm for patients not suitable for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
2
0
4
Order By: Relevance
“…Idiopathic HFS is a rare disorder with a 1 year prevalence of 1 in 10,000 people [4]. The cause of HFS is unclear, but it may be caused by a lesion such as a tumor, a cyst, an aneurysm, an AV malformation, an intrinsic brain stem lesion, or a bony lesion of the cranium in the cerebellopontine angle [2].…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic HFS is a rare disorder with a 1 year prevalence of 1 in 10,000 people [4]. The cause of HFS is unclear, but it may be caused by a lesion such as a tumor, a cyst, an aneurysm, an AV malformation, an intrinsic brain stem lesion, or a bony lesion of the cranium in the cerebellopontine angle [2].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-induced blockage of the paroxysmal ephaptic transmission in idiopathic trigeminal neuralgia may serve as an explanation for the relief from HFS after GKS. Fraioli et al 4 reported preliminary results of treat-ment of idiopathic HFS using radiosurgery or stereotactic hypofractionated radiotherapy and showed that a low radiation dose (8 Gy) directed to the facial nerve improved HFS. Kida et al 10 observed improvement in 5 of 7 pa- tients with facial or trigeminal nerve hyperfunction, despite the fact that tumor shrinkage was confirmed in only two patients.…”
Section: Mechanism Of Spasm Relief After Microsurgery and Radiosurgerymentioning
confidence: 99%
“…12 Entre as modalidades de tratamento, a abordagem clínica com carbamazepina ou toxina botulínica não mostra resultados tão satisfatórios a longo prazo como a descompressão microcirúrgica vascular na fossa posterior do crânio. 4,5,8,14 na intensidade dos espasmos. A tomografia computadorizada com uso de contraste não mostrou achados sugestivos de compressão do nervo facial.…”
Section: Introductionunclassified
“…No entanto, os benefícios da toxina botulínica são transitórios e decrescentes após múltiplas administrações 4 . O procedimento efetivo consiste na descompressão microvascular 4,5,8,14,17 .…”
Section: Introductionunclassified
See 1 more Smart Citation